PENGARUH PENANGANAN KELUHAN PELANGGAN DAN FITUR APLIKASI TERHADAP KEPUASAN PELANGGAN - Susianti, Dewi; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The development of Information Systems Technology in the field of health through the internet one of them is E-health. Applications that provide online Health Services one of them is Halodoc. This study aims to examine and analyze the effect of handling customer complaints on user satisfaction Halodoc in Malang and the effect of features on user satisfaction Halodoc in Malang. Determination of the number of samples using non-probability Sampling based on Purposive Sampling techniques and obtained 60 respondents. In this study, to measure customer satisfaction, Likert scale is used by using a measuring instrument in the form of questionnaires, interviews, literature studies, and internet browsing. The results showed that complaints (X2) partially handling complaints (X2) significantly affect user satisfaction (Y). Because the path coefficient marked positive (0.360) indicates the influence of both is positive or unidirectional, so H3 is accepted or significant. The results of the path analysis showed that the handling of complaints significantly affect user satisfaction. The results also showed that the application features offered to service users have a positive impact on the satisfaction of Halodoc application users in Malang.